Opsin spectral sensitivity determines the effectiveness of optogenetic termination of ventricular fibrillation in the human heart: a simulation study. (24th April 2016) - Karathanos, Thomas V.; Bayer, Jason D.; Wang, Dafang; Boyle, Patrick M.; Trayanova, Natalia A.
Abstract : Key points: Optogenetics‐based defibrillation, a theoretical alternative to electrotherapy, involves expression of light‐sensitive ion channels in the heart (via gene or cell therapy) and illumination of the cardiac surfaces (via implanted LED arrays) to elicit light‐induced activations. We used a biophysically detailed human ventricular model to determine whether such a therapy could terminate fibrillation (VF) and identify which combinations of light‐sensitive ion channel properties and illumination configurations would be effective. Defibrillation was successful when a large proportion (> 16.6%) of ventricular tissue was directly stimulated by light that was bright enough to induce an action potential in an uncoupled cell. While illumination with blue light never successfully terminated VF, illumination of red light‐sensitive ion channels with dense arrays of implanted red light sources resulted in successful defibrillation. Our results suggest that cardiac expression of red light‐sensitive ion channels is necessary for the development of effective optogenetics‐based defibrillation therapy using LED arrays. Abstract: Optogenetics‐based defibrillation has been proposed as a novel and potentially pain‐free approach to enable cardiomyocyte‐selective defibrillation in humans, but the feasibility of such a therapy remains unknown. This study aimed to (1) assess the feasibility of terminating sustained ventricular fibrillation (VF) via light‐induced excitation of opsins expressed throughout the myocardium and (2) identify the ideal (theoretically possible) opsin properties and light source configurations that would maximise therapeutic efficacy. We conducted electrophysiological simulations in an MRI‐based human ventricular model with VF induced by rapid pacing; light sensitisation via systemic, cardiac‐specific gene transfer of channelrhodopsin‐2 (ChR2) was simulated. In addition to the widely used blue light‐sensitive ChR2‐H134R, we also modelled theoretical ChR2 variants with augmented light sensitivity (ChR2+), red‐shifted spectral sensitivity (ChR2‐RED) or both (ChR2‐RED+). Light sources were modelled as synchronously activating LED arrays (LED radius: 1 mm; optical power: 10 mW mm –2 ; array density: 1.15–4.61 cm –2 ). For each unique optogenetic configuration, defibrillation was attempted with two different optical pulse durations (25 and 500 ms). VF termination was only successful for configurations involving ChR2‐RED and ChR2‐RED+ (for LED arrays with density ≥ 2.30 cm –2 ), suggesting that opsin spectral sensitivity was the most important determinant of optogenetic defibrillation efficacy. This was due to the deeper penetration of red light in cardiac tissue compared with blue light, which resulted in more widespread light‐induced propagating wavefronts. Longer pulse duration and higher LED array density were associated with increased optogenetic defibrillation efficacy. In all cases observed, the defibrillation mechanism was light‐induced depolarisation of the excitable gap, which led to block of reentrant wavefronts. Key points: Optogenetics‐based defibrillation, a theoretical alternative to electrotherapy, involves expression of light‐sensitive ion channels in the heart (via gene or cell therapy) and illumination of the cardiac surfaces (via implanted LED arrays) to elicit light‐induced activations. We used a biophysically detailed human ventricular model to determine whether such a therapy could terminate fibrillation (VF) and identify which combinations of light‐sensitive ion channel properties and illumination configurations would be effective. Defibrillation was successful when a large proportion (> 16.6%) of ventricular tissue was directly stimulated by light that was bright enough to induce an action potential in an uncoupled cell. While illumination with blue light never successfully terminated VF, illumination of red light‐sensitive ion channels with dense arrays of implanted red light sources resulted in successful defibrillation. Our results suggest that cardiac expression of red light‐sensitive ion channels is necessary for the development of effective optogenetics‐based defibrillation therapy using LED arrays.